Quasi-P wave through orthotropic piezo-thermoelastic materials subject to higher order fractional and memory-dependent derivatives - Gupta, Vipin; Barak, M. S. (Mechanics of advanced materials and structures, 2024)
This study uses the triple-phase lag model to investigate how higher-order fractional order and memory-dependent derivatives affect reflection at the free surface of an orthotropic piezo-thermoelastic medium. The performance of both kinds of derivatives is studied using the normal mode analysis technique. Four different types of coupled reflected plane waves are identified and explore the impact of various parameters, fractional order parameter, kernel function, the higher-order time differential fractional, and memory-dependent heat conduction parameters on energy distribution with respect to the angle of incidence. The results are presented graphically, providing numerical data for reflected waves, amplitude, and energy ratios.